2‐(Pyrazol‐4‐yl)‐1, 3‐oxaselenolanes from Pyrazole Сarbaldehydes and 2‐Selanyl‐1‐ethanol. Issue 1 (9th July 2014) - Papernaya, Lyubov K.; Shatrova, Alexandra A.; Levanova, Ekaterina P.; Albanov, Alexandr I.; Klyba, Lyudmila V.; Rudyakova, Elena V.; Levkovskaya, Galina G.
ABSTRACT Pyrazole carbaldehydes react with 2‐selanyl‐1‐ethanol at room temperature in the presence of trimethylchlorosilane followed by treatment with triethyl amine to afford the corresponding 2‐(pyrazol‐4‐yl)‐1, 3‐oxaselenolanes. The structure of the novel compounds was confirmed by IR, 13C, 1H, 15N, and 77Se NMR spectroscopy.